Review—Graded Catalyst Layers in Hydrogen Fuel Cells - A Pathway to Application-Tailored Cells - Ayoub, Marc; Böhm, Thomas; Bierling, Markus; Thiele, Simon; Brodt, Matthew (Journal of The Electrochemical Society, 2024)
During steady-state operation, the proton conduction profile and the concentration profiles of the reactants and products transported through catalyst layers are non-uniform in the in-plane and through-plane directions. It is, therefore, a reasonable hypothesis that the optimal arrangement of the constituents of the catalyst layers should also be non-uniform. One way to address the non-uniformity is through graded catalyst layers. This study elucidates the state-of-the-art for graded catalyst layers, which so far were primarily investigated for proton exchange membrane fuel cells (PEMFCs). We identify the most impactful types of gradients in the PEMFC cathode and highlight studies displaying their merits in terms of better conversion efficiencies and longer lifetimes. Furthermore, two critical issues that have received little attention so far are emphasized: on the one hand, industrially relevant manufacturing techniques must be developed and implemented. On the other hand, suitable techniques are needed to identify and characterize the gradients. In this study, guidance to navigate both of these challenges is offered.
CRIS-Team Scopus Importer:2024-09-20
Keywords: coatings; energy conversion; fuel cells - PEM